Effects of bacterial cultures, enzymes, and yeast-based feed additive combinations on ruminal fermentation in a dual-flow continuous culture system - Bennett, S. L.; Arce-Cordero, J. A.; Brandao, V. L.N.; Vinyard, J. R.; Agustinho, B. C.; Monteiro, H. F.; Lobo, R. R.; Tomaz, L. [UNESP]; Faciola, A. P. (Oxford University Press (OUP), 2021)
Bacterial cultures, enzymes, and yeast-derived feed additives are often included in commercial dairy rations due to their effects on ruminal fermentation. However, the effects of these additives when fed together are not well understood. The objective of this study was to evaluate the changes in ruminal fermentation when a dairy ration is supplemented with combinations of bacterial probiotics, enzymes and yeast. Our hypotheses were that ruminal fermentation would be altered, indicated through changes in volatile fatty acid profile and nutrient digestibility, with the inclusion of (1) an additive, (2) yeast, and (3) increasing additive doses. Treatments were randomly assigned to 8 fermenters in a replicated 4 × 4 Latin square with four 10 d experimental periods, consisting of 7 d for diet adaptation and 3 d for sample collection. Basal diets contained 52:48 forage:concentrate and fermenters were fed 106 g of dry matter per day divided equally between two feeding times. Treatments were: control (CTRL, without additives); bacterial culture/enzyme blend (EB, 1.7 mg/d); bacterial culture/enzyme blend with a blend of live yeast and yeast culture (EBY, 49.76 mg/d); and a double dose of the EBY treatment (2×, 99.53 mg/d). The bacterial culture/enzyme blend contained five strains of probiotics (Lactobacillus animalis, Propionibacterium freudenreichii, Bacillus lichenformis, Bacillus subtilis, and Enterococcus faecium) and three enzymes (amylase, hemicellulase, and xylanase). On d 8-10, samples were collected for pH, redox, volatile fatty acids, lactate, ammonia N, and digestibility measurements. Statistical analysis was performed using the GLIMMIX procedure of SAS. Repeated measures were used for pH, redox, VFA, NH3-N, and lactate kinetics data. Orthogonal contrasts were used to test the effect of (1) additives, ADD (CTRL vs. EB, EBY, and 2X); (2) yeast, YEAST (EB vs. EBY, and 2X); and (3) dose, DOSE (EBY vs. 2X). No effects (P > 0.05) were observed for pH, redox, NH3-N, acetate, isobutyrate, valerate, total VFA, acetate:propionate, nutrient digestibility or N utilization. Within the 24 h pool, the molar proportion of butyrate increased (P = 0.03) with the inclusion of additives when compared to the control while the molar proportion of propionate tended to decrease (P = 0.07). In conclusion, the inclusion of bacterial cultures, enzymes and yeast in the diet increased butyrate concentration; but did not result in major changes in ruminal fermentation.
Keywords: amylase; butyrate; hemicellulase; Saccharomyces cerevisiae; xylanase